KARAKTERISTIK CAMPURAN ASPHALTIC CONCRETE WEARING COURSE (AC-WC) MENGGUNAKAN KOMBINASI BAHAN PENGISI (FILLER) - Yasruddin, Yasruddin (Jurnal Teknologi Berkelanjutan, 2020)
Currently, Asphaltic Concrete (AC) is widely used as a surface layer in road construction in Indonesia because of its waterproof, durable, structural value and can be used for light to heavy traffic. There are various asphalt mixtures, such as hot asphalt mixtures using rock ash filler, cement and lime on the surface layer of the Asphaltic Concrete Wearing Course (AC-WC). Therefore, it is necessary to conduct research to determine Marshall characteristics in the evaluation of hot asphalt mixtures using rock ash, cement and lime fillers on the Asphaltic Concrete Wearing Course (AC-WC) surface layer which is adjusted to the specifications of Indoneisan Highways. Marshall test results on the AC-WC mixture using 3 different types of filler such as rock ash filler, cement and lime with Marshall parameters. In the stone ash filler test, the optimum asphalt content was 5.8% with Marshall parameters namely Stability (1180 kg), Flow (3.75mm), MQ (339kg/mm), VIM (4.75%), VMA (17.4 %), VFB (79.5%). For Cement Filler, the optimum asphalt content is 5.7% with Marshall parameters namely Stability (980 kg), Flow (3.8mm), MQ (260kg/mm), VIM (5.26%), VMA (17.8% ), VFB (75%). As for the Lime Filler, the optimum asphalt content was 6.6% with Marshall parameters namely Stability (1060 kg), Flow (3.7mm), MQ (310kg/mm), VIM (5.25%), VMA (19%), VFB (79%). In addition, the Marshall immersion test with IRS values obtained results of 88.45%, 91.52% and 84.36% for rock ash filler, cement filler, and lime filler respectively, where all results meet the minimum specification requirements of 75% based on Indoneisan Highways specification.